THE ROLE OF THE CONGNITEVE AND EXPRESSIVE LANGUAGE FUNCTION IN REALISATION OF THE CATEGORY OF INTENSITY - Rys, U. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
This paper examines the theoretical basis of the interconnection of cognitive and expressive language functions, as well as reveals the substance of terms “expression”, “emotion”, “cognition” and their role in creation of the category of intensity. The study concentrates on the cognitive and linguistic aspects of the category of intensity.